Short-Segment Instrumentation with Fractured Vertebrae Augmentation by Screws and Bone Substitute for Thoracolumbar Unstable Burst Fractures. (27th December 2019) - Liao, Jen-Chung; Chen, Wen-Jer
Abstract : Background . For thoracolumbar burst fractures, traditional four-screw (one above and one below) short-segment instrumentation is popular and has a high failure rate. Additional augmentation at the fractured vertebrae is believed to reduce surgical failure. The purpose of this study was to examine the clinical and radiographic results of patients who underwent short-segment posterior instrumentation with augmentation by screws and bone substitutes at the fractured vertebrae and to compare these data to those of patients who underwent long-segment instrumentation for thoracolumbar burst fractures. Methods . The study group had twenty patients who underwent short-segment instrumentation with additional augmentation by two screws and bone substitutes at the fractured vertebrae. The control group contained twenty-two patients who underwent eight-screw long instrumentation without vertebra augmentation. Local kyphosis and the anterior body height of the fractured vertebrae were measured. The severity of the fractured vertebrae was evaluated with the load sharing classification (LSC). Any implant failure or loss of correction >10° at the final follow-up was defined as surgical failure. Results . Both groups had similar distributions in terms of age, sex, the injured level, and the mechanism of injury before operation. During the operation, the study group had significantly less blood loss (136.0 vs. 363.6 ml, p = 0.001 ) and required shorter operating times (146.8 vs. 157.5 minutes, p = 0.112 ) than the control group. Immediately after surgery, the study group had better correction of the local kyphosis angle (13.4° vs. 11.9°, p = 0.212 ) and restoration of the anterior height (34.7% vs. 31.0%, p = 0.326 ) than the control group. At the final follow-up, no patients in the study group and only one patient in the control group experienced surgical failure. Conclusions . Patients with thoracolumbar burst fractures who received six-screw short-segment posterior fixators with augmentation at the level of the fractured vertebrae via injectable artificial bone substitute achieved satisfactory clinical and radiographic results, and this method could replace long-segment instrumentation methods used in unstable thoracolumbar burst fractures.